The Effect of Work Environment, Work Motivation and Career Development on Performance (Literature Reviews) - Lestari, Dwi (Dinasti International Journal of Digital Business Management, 2023)
This article's literature study aims to develop a hypothesis about the relationship between the variables Work Environment, Work Motivation, and Career Development with Performance in the Field of Human Resource Management. This article was written using the library research method using sources from online media such as Google Scholar, Mendeley, and other online academic sources. From this literature review article, it can be concluded that there are three influences between variables, namely: 1) Work Environment affects Performance; 2) Work Motivation affects Performance; and 3) Career Development affects Performance.